2014
DOI: 10.14257/ijhit.2014.7.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying Intelligent Daily Environments through Introducing Fictionality

Abstract: A virtual form is an abstraction that enhances existing products and services by adding a layer to virtualize them. From a technical point of view, the current information technologies already make it possible to develop a virtual form using various techniques that represent information such as augmented reality technologies or ubiquitous display technologies. The virtual form can return a immediate feedback to a user so that it becomes a good design tool to develop games deployed in public spaces.We believe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several authors have suggested that adding (fictional) stories to a design is an important dimension of gameful or playful design to drive engagement (Dickey 2006;Reeves and Read 2009;Langer et al 2013;Sakamoto and Nakajima 2014). One relatively common genre are tourism-focused mixed reality applications like REXplorer (Ballagas et al 2008)o rVoices of Oakland (Dow et al 2005).…”
Section: Storificationmentioning
confidence: 99%
“…Several authors have suggested that adding (fictional) stories to a design is an important dimension of gameful or playful design to drive engagement (Dickey 2006;Reeves and Read 2009;Langer et al 2013;Sakamoto and Nakajima 2014). One relatively common genre are tourism-focused mixed reality applications like REXplorer (Ballagas et al 2008)o rVoices of Oakland (Dow et al 2005).…”
Section: Storificationmentioning
confidence: 99%